Simulation of a model DC-DC converter with cascaded via improvement PFC with boost converter and THD using multiple loads. (19th March 2020) - Yadav, Anchal; Tiwari, Pratibha
In this paper proposed a converter which improves the total harmonic distortion (THD) and power factor correction (PFC). In proposed DC side boost converter accompany through the forward converter. In this research, conventional rectifier's diode-bridge and rectifying bridge linked with boost converters which given good performance of the system. So it is concluded the improvement of total harmonic factor and power factor through the solution of the simulation. It is reduce the input current with proposed converter, and minimise the current harmonic. Instantly enlarge power semiconductors devices with utilisation of power electronics systems, which generate broad and new applications ranges like, aerospace, commercial, industrial and traction. The semi-converter device connected with current drawn which given line distortion results in high level of harmonics and low power factor. More analysis of these problems always connected with multiple loads and nonlinear utilisation of load input current with total harmonic distortion.